Merancang Bangun Aplikasi e-JO Berbasis Website Departemen Instalasi PT. ANDS - Aurora, Diva Herna; Cahyono, M. Ridwan Arif; Susilawati, Dera (Prodi D3 Teknik Elektronika Politeknik Gajah Tunggal, 2025)
The submission of job orders for repairs, new machine installations, modifications, and machine relocations is currently done manually using paper. This manual process causes delays in job order delivery, difficulties in monitoring the progress of job orders, and challenges in finding and archiving job order forms. To address these issues, this study designed a web-based e-JO system using the CodeIgniter framework and MySQL database. The system aims to make the process more efficient and structured. After implementing the e-JO system, data was collected to measure potential time savings. The results showed that before the change, the job order submission process took 17,287 seconds, whereas after the new system was implemented, it only took 1,137 seconds. Thus, it can be concluded that the e-JO system significantly reduced the job order submission time, making the process faster and more efficient.